2015
DOI: 10.1002/cmdc.201500269
|View full text |Cite
|
Sign up to set email alerts
|

Potent and Selective Human Neutrophil Elastase Inhibitors with Novel Equatorial Ring Topology: in vivo Efficacy of the Polar Pyrimidopyridazine BAY‐8040 in a Pulmonary Arterial Hypertension Rat Model

Abstract: Human neutrophil elastase (HNE) is a key driver of inflammation in many cardiopulmonary and systemic inflammatory and autoimmune conditions. Overshooting high HNE activity is the consequence of a disrupted protease-antiprotease balance. Accordingly, there has been an intensive search for potent and selective HNE inhibitors with suitable pharmacokinetics that would allowing oral administration in patients. Based on the chemical probe BAY-678 and the clinical candidate BAY 85-8501 we explored further ring topolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…In the few published reports, it could be shown that specific proteins expressed by neutrophils, such as myeloperoxidase (MPO) and neutrophil elastase (NE), are elevated in peripheral plasma from PH patients and correlated with the severity of PAH and clinical outcome [ 130 ]. Selective NE inhibitors attenuated or even reversed PAH and pulmonary vascular remodeling in the rat model of monocrotaline-induced PAH, and they are the focus of current clinical investigation [ 131 , 132 ]. Even more exciting from a clinical perspective, late intervention with an MPO inhibitor stopped the progression of experimental chronic obstructive pulmonary disease and partially protected against PAH [ 132 ].…”
Section: Inflammatory Mediators and Their Effects On Vascular Remomentioning
confidence: 99%
“…In the few published reports, it could be shown that specific proteins expressed by neutrophils, such as myeloperoxidase (MPO) and neutrophil elastase (NE), are elevated in peripheral plasma from PH patients and correlated with the severity of PAH and clinical outcome [ 130 ]. Selective NE inhibitors attenuated or even reversed PAH and pulmonary vascular remodeling in the rat model of monocrotaline-induced PAH, and they are the focus of current clinical investigation [ 131 , 132 ]. Even more exciting from a clinical perspective, late intervention with an MPO inhibitor stopped the progression of experimental chronic obstructive pulmonary disease and partially protected against PAH [ 132 ].…”
Section: Inflammatory Mediators and Their Effects On Vascular Remomentioning
confidence: 99%
“…AZD9668 and BAY 85-8501 are in clinical trials (Phase II) for the treatment of patients with CF, COPD, bronchiectasis and pulmonary disease 18 , 76 , 80 . BAY-8040 showed excellent potency, selectivity, and improved the cardiac function in a rat model 81 .…”
Section: Exogenous and Therapeutic Neutrophil Serine Protease Inhibitmentioning
confidence: 94%
“…The proteolytic activity of serine proteases, which is essential for the maintenance of important host functions, can also be harmful if not properly regulated, and a number of regulatory mechanisms are present (Von Nussbaum et al, ). For example, these proteases are stored as inactive precursors in specialized compartments, such as azurophil granules for serine proteases.…”
Section: Introductionmentioning
confidence: 99%